Ebola Virus Epidemic in West Africa and Beyond - Oscar G Gómez-Duarte (Revista de la Facultad de Medicina, 2014)
Is there a reason to fear that an Ebola outbreak may strike Latin America? The fear may not be unreasonable taking into account the history of epidemics that have affected the American continent since colonization times in 1492. Old World small pox epidemics spread and killed millions of Native Americans north and south from the equator. Imported West Nile virus infections reported in New York in 1999 dramatically spread East to West of the United States. Most recently, Chikungunya virus arrived to Central America in 2013 and has already infected close to 1 million people in Mexico, Central American countries, Brazil, Colombia, Ecuador, Guyanas, Paraguay, and Venezuela.